Um estudo sobre as ações de avaliação da aprendizagem e intervenções pedagógicas desenvolvidas com crianças não alfabetizadas em turmas de 4º ano do E.F. em uma escola do município de Fortaleza/CE - Lima, Nágila Rabelo de (2018)
The results of the external evaluations of the National Literacy Assessment - ANA and the Brazil Proof for the Portuguese Language disciplines have shown that there are students who complete the 3rd year of Elementary School (EF) and arrive until the 5th year without being properly literate - which interferes directly with their school performance. In this sense, pedagogical intervention strategies are presented as essential for overcoming learning deficits. Based on this premise, this research investigated the evaluation actions and strategies of pedagogical intervention developed with 4th grade students identified as not literate in a school in the city of Fortaleza, CE, with low performance in the external evaluations of Portuguese Language (ANA-2013 and Brazil Proof "5th year" - 2015). The qualitative and descriptive research methodology included the application of reading and writing activities with non-literate 4th year students, interviews with the pedagogical coordination of the school and teachers-regents, as well as observation techniques in Language classes Portuguese teachers taught by the regent teachers and support focused on interventions aimed at the difficulties of the non-literate students. The results showed that the school develops improvement actions for the recovery of non-literate students, however, due to the nonsystematization of the strategic actions, no significant improvements were noticed, since the reading and writing activities applied to 8 (eight) students in the November to December / 2017 also detected serious problems of literacy. In addition, the research showed that the support teachers did not develop activities focused on the difficulties of the students, while the teachers-regents, although presenting methodologies that contribute to the literacy and literacy process of the children, were unable to develop differentiated activities at the same time. order to meet the cognitive level of non-literate students in the classroom. We conclude that the strategies, for the time being observed, need to be better systematized, adequate didactic resources and results monitoring.